2018
DOI: 10.1093/ntr/ntx274
|View full text |Cite
|
Sign up to set email alerts
|

Little Cigars, Filtered Cigars, and their Carbonyl Delivery Relative to Cigarettes

Abstract: IntroductionLittle cigars and filtered cigars are currently growing in popularity due to their low cost and wide variety of flavors while retaining an appearance similar to cigarettes. Given the health consequences associated with cigarette use, it is important to understand the potential harm associated with these similar products. This includes the potential harm associated with carbonyls (eg, acetaldehyde, acrolein, formaldehyde, etc.), an important class of toxicants and carcinogens in tobacco smoke. Our o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“… 26 Focusing on the products themselves, Reilly et al examined two brands each of little cigars and filtered cigars, as well as two research cigarettes for carbonyl delivery and found that cigar smokers are exposed to higher levels of carbonyls per cigar than cigarette smokers per cigarette. 27 These data advance an understanding of the potential relative harm from carbonyl exposure for cigar-only smokers and the cumulative harm among the population of cigarette–cigar polytobacco users. 27 …”
Section: Addiction and Toxicitymentioning
confidence: 83%
See 2 more Smart Citations
“… 26 Focusing on the products themselves, Reilly et al examined two brands each of little cigars and filtered cigars, as well as two research cigarettes for carbonyl delivery and found that cigar smokers are exposed to higher levels of carbonyls per cigar than cigarette smokers per cigarette. 27 These data advance an understanding of the potential relative harm from carbonyl exposure for cigar-only smokers and the cumulative harm among the population of cigarette–cigar polytobacco users. 27 …”
Section: Addiction and Toxicitymentioning
confidence: 83%
“… 27 These data advance an understanding of the potential relative harm from carbonyl exposure for cigar-only smokers and the cumulative harm among the population of cigarette–cigar polytobacco users. 27 …”
Section: Addiction and Toxicitymentioning
confidence: 83%
See 1 more Smart Citation
“…Our results are consistent with previous publications analyzing carbonyl content in smoke produced from conventional and reference tobacco cigarettes using the HCI regime. 19,[25][26][27][28] In all pairwise comparisons of the Brand A cigarette, the smoke contained significantly lower yields of acetaldehyde, acetone, propionaldehyde, and 2-butanone (Figs. 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies did not examine characteristics that predicted whether women continued smoking cigarettes, transitioned to ENDS, or quit all tobacco. Identifying those variables associated with continued use of cigarettes and/or other combusted products used like cigarettes (i.e., filtered cigars and cigarillos) (Reilly et al, 2018;Richardson et al, 2012), transitioning to ENDS, or quitting tobacco, could provide valuable insights to policymakers at the FDA. The FDA extended their authority to regulate ENDS in 2016 (United States Food and Drug Administration, 2016) and await research that informs regulatory policy surrounding these products.…”
Section: Introductionmentioning
confidence: 99%